2011
DOI: 10.1177/1527476411424419
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of Insecurity

Abstract: This article discusses the working lives of individuals working in the British independent television production sector. It focuses on the material reality of their individualised, precarious working environment, investigating the disjuncture between the precarious, insecure nature of creative labour within this industry, which engenders stress and anxiety, and the intense emotional pleasure associated with such work. While the tension between ‘pleasure’ and ‘pain’ within creative occupations has been well doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…It entails the accepting of longer hours and lower pay for achieving these laudatory aims (Bloom, 2017: 171). Lee (2012) sees this in his respondents, where:…”
Section: Ethical Relationshipsmentioning
confidence: 97%
“…It entails the accepting of longer hours and lower pay for achieving these laudatory aims (Bloom, 2017: 171). Lee (2012) sees this in his respondents, where:…”
Section: Ethical Relationshipsmentioning
confidence: 97%
“…A collapse in ratings and increased competition for advertising revenue are among the factors that have led to dwindling budgets and schedules, which pile pressure on producers to meet high expectations with fewer resources (Hesmondhalgh, 2018; Ursell, 2000). Lee (2012) suggests that ethical behaviour towards participants becomes harder to sustain in such circumstances, claiming ‘the moral core of television is being corroded from within because of the transformed institutional, economic and political context within which it is taking place’ (p. 494). However, empirical research has tended to approach the issue from the perspective of creative workers rather than contributors.…”
Section: Working Practices and The Production Environmentmentioning
confidence: 99%
“…A significant thread of scholarship has focussed on the impact of these changes upon creative workers, whose working conditions have undergone a parallel transition: evolving from a stable, unionised workforce of direct employees, to a deregulated environment, where the pleasures of producing creative work are offset against considerable stress and anxiety (Hesmondhalgh and Baker, 2011). Risk is devolved from companies to individuals, who operate in conditions of chronic precarity and insecurity (Lee, 2012). In the UK, recently published research by the Screen Industries Growth Network found that on average, TV workers put in the equivalent of two extra working days per week in excess of the general population (Swords et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Townley et al. (2009), for instance, note that especially in television and film production, “creative labor no longer has an organizational buffer against the inherent risk and uncertainty of project‐based employment” (p. 951) (see also Blair, 2009; Lee, 2012). The risks associated with employment and income insecurity are key drivers of intersectional inequality in screen industries labor markets.…”
Section: Inequality and Riskmentioning
confidence: 99%
“…Individuals' opportunities to make a living in the cultural and creative industries are shaped by risk: the prevalence of project-based production results in widespread income and employment insecurity and in substantive risks of not being able to provide for one's livelihood (e.g., Banks et al, 2000). Townley et al (2009), for instance, note that especially in television and film production, "creative labor no longer has an organizational buffer against the inherent risk and uncertainty of project-based employment" (p. 951) (see also Blair, 2009;Lee, 2012). The risks associated with employment and income insecurity are key drivers of intersectional inequality in screen industries labor markets.…”
Section: Inequality and Riskmentioning
confidence: 99%